Evaluation of the Lighting System on Boeing 737-300 Aircraft PT. Mulya Sejahtera Technology Bandung - Riadi Parasian Sirait; Catra Indra Cahyadi; Rofi Juliatma; Ayub Wimatra (International Journal of Sustainable Engineering Innovations, 2025)
Background of study: Aircraft maintenance is vital for flight safety. To connect theory with practice, students at Medan Aviation Polytechnic undergo Field Work Practice at PT. Mulya Sejahtera Technology, focusing on aircraft lighting systems. Aims and scope of paper: This paper discusses the evaluation of the Boeing 737-300 lighting system at PT. Mulya Sejahtera Technology Bandung, based on Field Work Practice involving trainees in maintenance, inspection, and troubleshooting across multiple divisions. Methods: Using a descriptive observational approach, trainees engage in one month of daily maintenance, document tasks, and receive supervisor evaluations. Data is gathered through observation, practice, and feedback. Result: Fieldwork Practice provides valuable hands-on experience, which significantly enhances trainees' technical skills, problem-solving abilities, and understanding of the complexity and importance of lighting systems. Trainees successfully apply classroom theory into real-life maintenance scenarios, develop effective communication skills, and adapt to a professional work environment. Conclusion: Evaluation of the Boeing 737-300 lighting system at PT. Mulya Sejahtera Technology Bandung confirms its crucial role in flight safety and comfort. While most components meet standards, some require periodic maintenance and replacement due to aging. Routine inspections are essential to maintain optimal performance and regulatory compliance.